The Role of Law Firms in Ensuring the Suspect's Right to Effective Legal Assistance in Criminal Cases - Tarigan, David Marcel; Siregar, Hisar (The Future of Education Journal, 2026)
The fulfillment of a suspect’s right to effective legal assistance is a crucial element in ensuring a fair criminal justice system grounded in human rights protection. In practice, suspects often face an unequal position when dealing with law enforcement authorities, which highlights the importance of professional and continuous legal representation. This article aims to examine the role of law firms in guaranteeing suspects’ rights to effective legal assistance in criminal cases and to identify the obstacles encountered in its implementation. This study employs normative legal research using statutory and conceptual approaches. Legal materials consist of primary, secondary, and tertiary sources collected through library research and analyzed qualitatively through legal reasoning. The discussion reveals that law firms play a strategic role as institutions, media, and service providers that perform legal protection, legal education, defense planning, psychological assistance, supervision of judicial processes, and the pursuit of legal remedies. Nevertheless, the effectiveness of these roles is constrained by structural, institutional, and cultural challenges, including limited access, insufficient resources, external pressures, and a legal culture that does not fully support the role of defense counsel. Therefore, strengthening the institutional capacity of law firms and reforming the criminal justice system are essential steps toward ensuring effective legal assistance and achieving substantive justice for suspects.